Holmes and Jane Rolston: memories and recollections: part 2 - Rolston, Holmes, 1932-2025, interviewee; Rolston, Jane, interviewee; Rolston, David, interviewer (Colorado State University. Libraries, 2009)
Memories and recollections by Holmes Rolston III and his wife Jane Irving Wilson Rolston interviewed in their home, Fort Collins, Colorado, October 25 2009, by David Rolston, a relative. Disk 2 covers Holmes' Rolston career as Professor of Philosophy, Colorado State University, University Distinguished Professor; Rolston's books and publications, Gifford Lectures, University of Edinburgh, 1997-1998; Templeton Prize, 2003; Intellectual Biography, Saving Creation, 2009.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Rolston, Jane Irving, 1931-2025; Rolston, Holmes, 1932-2025